The introduced terrestrial slugs Ambigolimax nyctelius (Bourguignat, 1861) and Ambigolimax valentianus (Férussac, 1821) (Gastropoda: Limacidae) in California, with a discussion of taxonomy, systematics, and discovery by citizen science. Issue 25 (11th July 2019) - Vendetti, Jann E.; Burnett, Emily; Carlton, Lidia; Curran, Anne T.; Lee, Cedric; Matsumoto, Ron; Mc Donnell, Rory; Reich, Inga; Willadsen, Ole
ABSTRACT: Ambigolimax valentianus and Ambigolimax nyctelius are synanthropic terrestrial slugs that have been dispersed widely by human activity. Herein, these species are reported from Los Angeles County, California, as a result of contributions to SLIME (Snails and Slugs Living in Metropolitan Environments), a citizen science project initiated by the Natural History Museum of Los Angeles County and hosted online by iNaturalist. Importantly, collected specimens and specimen data of A. nyctelius are the first of this species in California and the first records to document it in North America since 1960. Species identifications of A. valentianus and A. nyctelius, which are phenotypically similar, were made by examination of specimens' distal genitalia and analysis of their mtDNA barcoding gene, COI ( A. nyctelius, n = 18 and A. valentianus, n = 11). Slug radulae and jaws were examined and are figured, but were not diagnostic to species. Phylogenetic analyses of COI haplotypes from both Ambigolimax species and six other limacids resolve A. nyctelius and A. valentianus as monophyletic sister taxa. However, morphological and molecular data from taxa not included in this study are needed to substantiate this relationship and inform a revision of at least 10 genera in the family Limacidae. Inconsistencies in the literature regarding the year of Férussac's species description of A. valentianus (as Limax valentianus ) are also discussed and resolved.